Combined Power Plants Applying Renewable Sources of Energy - M. M. Oleshkevich; Y. V. Makosko; V. M. Oleshkevich; P. L. Falioushin; N. I. Bokhan (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers combined power plants applying renewable sources of energy. It describes a number of conceptions for optimization of combined power plants consisting of wind- power and bioenergetics units. Calculations of power generation and evaluation of economical efficiency have been performed.